Animal models of the placenta accreta spectrum: current status and further perspectives - Ma, Yongdan; Hu, Yongyan; Ma, Jingmei (Frontiers in Endocrinology, 2023)
Placenta accreta spectrum disorder (PAS) is a kind of disease of placentation defined as abnormal trophoblast invasion of part or all of the placenta into the myometrium, even penetrating the uterus. Decidual deficiency, abnormal vascular remodelling in the maternal-fetal interface, and excessive invasion by extravillous trophoblast (EVT) cells contribute to its onset. However, the mechanisms and signaling pathways underlying such phenotypes are not fully understood, partly due to the lack of suitable experimental animal models. Appropriate animal models will facilitate the comprehensive and systematic elucidation of the pathogenesis of PAS. Due to the remarkably similar functional placental villous units and hemochorial placentation to humans, the current animal models of PAS are based on mice. There are various mouse models induced by uterine surgery to simulate different phenotypes of PAS, such as excessive invasion of EVT or immune disturbance at the maternal-fetal interface, which could define the pathological mechanism of PAS from the perspective of the “soil”. Additionally, genetically modified mouse models could be used to study PAS, which is helpful to explore the pathogenesis of PAS from the perspectives of both “soil” and “seed”, respectively. This review details early placental development in mice and humans, with a focus on the approaches of PAS modelling. Additionally, the strengths and limitations of each strategy and further perspectives are summarized to provide the theoretical foundation for researchers to select appropriate animal models for various research purposes. This will help better determine the pathogenesis of PAS and even promote possible therapy.